The Effect of Motivation and Perceived Organizational Support on Organizational Citizenship Behavior of The General Secretariat DPR RI Employees Mediated by Job Satisfaction - Siresia, Firosa; Riyanto, Setyo (Archives of Business Research, 2024)
This study aims to determine the influence between Motivation and Perceived Organizational Support on Organizational Citizenship Behavior in Employees of the Secretariat General of the DPR RI Mediated by Job Satisfaction. The population in this study consists of 104 Civil Servants in the Bureau of Building and Housing Management of the Secretariat General of the Indonesian House of Representatives (DPR RI). The study uses a saturated sampling method or cencus, thus the entire population is used as the research sample. Data analysis in this study utilizes Structural Equation Modeling (SEM) technique. The results indicate that Motivation has a positive and significant influence on job satisfaction. Perceived Organizational Support has a positive and significant influence on Job Satisfaction. Motivation has a positive and significant influence on Organizational Citizenship Behavior. Perceived Organizational Support has a positive and significant influence on Organizational Citizenship Behavior. Job Satisfaction has a positive and significant influence on Organizational Citizenship Behavior. Motivation has a positive and significant influence on Organizational Citizenship Behavior mediated by Job Satisfaction. Perceived Organizational Support has a positive and significant influence on Organizational Citizenship Behavior mediated by Job Satisfaction. This study contributes novelty as the first research to measure the level of OCB among employees in the Secretariat General of the Indonesian House of Representatives. This study provides novelty as the first research to measure the level of OCB among employess with in the Secretariat General of the Indonesian House of Representatives.